Dehumanization of Multicharacter Figures in Ludruk Traditional Art as Symbols of Imperialist Mental Agitation: A Case Study of the Play Sarip Tambak Oso - Sugit Zulianto; Juairiah Juairiah (Javanologi: International Journal of Javanese Studies, 2023)
In the story of the ludruk play which is legendary in Java-Indonesia, Sarip Tambak Oso is chased and captured by the invaders. He is claimed to be a criminal who is very humiliated. However, the Javanese people immortalized him as a public figure with character because of his concern and courage in defending the rights of the poor who were wronged by the colonial government. This research has a qualitative approach with a case study type. The main problem is, how is the multi-character of Sarip Tambak Oso's play dehumanized by the colonialists? For this reason, the data source is in the form of documents, both printed (published manuscripts) and electronic (ludruk performances with the play Sarip Tambak Oso). The research data is in the form of language (expressions, words, phrases, sentences) in the story. Next, verbal data is described qualitatively. The results showed that Sarip Tambak Oso had the characters of (1) caring, (2) devotion, (3) nationalism, and (4) religious, and (5) fair. In conclusion, the five characters are necessary when dealing with colonial era invaders. In fact, now, its fluctuating actualization needs to be considered as thoroughly as possible in the millennial era. This is necessary because the dehumanization of the multi-characteristics of public figures is not a natural characteristic of the Javanese nation in the world, except when fighting for national independence, as exemplified by Sarip Tambak Oso in East Java, Indonesia.Keywords: dehumanization, characters, Sarip Tambak Oso, imperialism, ludruk plays, Javanese oral literature